Geopolymer material for solidifying heavy metal contaminated soil and preparation method thereof

By introducing sodium alginate into the geological polymer material, the reinforced composite geological polymer material is solved, and the curing/stabilization effect of contaminated soil is significantly improved.

CN119797788AActive Publication Date: 2025-04-11TIANFU YONGXING LAB +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510311034.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-11
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The prior art has problems such as low compressive strength, high leaching concentration and unstable heavy metals when curing heavy metal contaminated soil.

Method used

Sodium alginate reinforced composite geological polymer material is used to mix sodium alginate with red mud, desulfurization gypsum and fly ash and process it in an alkali trigger to form N-A-S-H and C-A-S-H gels to enhance the compressive strength and heavy metal resistance of the material.

Benefits of technology

It significantly improves the compressive strength of the contaminated soil, reduces the leaching concentration of heavy metals, and converts heavy metals into a more stable form, improving the curing/stabilization effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797788A_ABST
    Figure CN119797788A_ABST
Patent Text Reader

Abstract

The invention discloses a geopolymer material for solidifying heavy metal contaminated soil and a preparation method thereof, and belongs to the field of soil pollution abatement, the geopolymer material comprises the following components by weight: 100 parts of a geopolymer precursor; 2-5 parts of sodium alginate; 13 to 15 parts of an alkali activator; 60 to 62 parts of water; the alkali activator is a water glass solution with the modulus of 1.4; the geopolymer precursor comprises the following components in percentage by weight: 45-55 wt.% of red mud; 5 wt.% to 15 wt.% of desulfurized gypsum; the problems that in the prior art, the compressive strength is low, and the metal leaching concentration is high and unstable are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of soil pollution control, and in particular to a geopolymer material for solidifying heavy metal contaminated soil and a preparation method thereof. Background Art

[0002] With the extensive mining of mineral resources, the large amount of waste tailings has become a global environmental problem. These tailings contain toxic heavy metals, such as lead (Pb 2+ )、Zn(Zn 2+ ), copper (Cu 2+ ) and cadmium (Cd 2+ ), etc., are easily migrated and spread from the soil during the stacking process, posing a threat to the surrounding ecological environment and human health. Therefore, effective stabilization of these tailings to prevent further environmental pollution by heavy metals has become a technical problem that urgently needs to be solved.

[0003] As an effective contaminated soil treatment technology, solidification / stabilization technology adds a solidifying agent to the contaminated soil to make it react physically and chemically with the heavy metals in the soil to form a solidified / stabilized product with a dense structure, strong compressive resistance and low permeability, thereby reducing the mobility of heavy metals in the soil and achieving the safety level specified in the remediation target. The Chinese patent with publication number CN106477985A discloses a red mud geopolymer material formula and a preparation method thereof, with red mud and fly ash as basic raw materials, water glass solution and alkaline solution as activators, and the material ratio is based on the mass ratio of red mud: fly ash: water glass solution: alkaline solution = 1: 1: 0.7: (0.25-0.3). The red mud-based geopolymer material was prepared at room temperature, and the maximum strength at 28d can reach more than 40MPa. The Chinese patent with publication number CN114988728A discloses a method for fixing arsenic in neutralized slag using fly ash-red mud-based polymers, wherein fly ash, red mud and desulfurized gypsum are mixed evenly to obtain a fly ash-red mud mixture, sodium hydroxide is dissolved in a calcium hydroxide solution, and the mixture is allowed to stand for 5 to 10 hours to obtain an alkali activator; the alkali activator is added to the fly ash-red mud mixture, and then the neutralized slag is added and mixed evenly to obtain a slurry; the slurry is injected into a mold and sealed and allowed to stand at room temperature for 30 to 33 hours, and after demolding, it is placed at room temperature and a humidity of 80 to 90% for more than 7 to 28 days to obtain an arsenic-containing solid. However, the above technical solution has the disadvantages of large amount of curing agent added, low compressive strength, high heavy metal leaching concentration, and instability. Summary of the invention

[0004] The invention provides a geopolymer material for solidifying heavy metal contaminated soil and a preparation method thereof, which solves the problems of low compressive strength and high and unstable metal leaching concentration in the prior art.

[0005] In order to solve this technical problem, the present invention provides the following technical solution: The geopolymer material for solidifying heavy metal contaminated soil comprises the following components in parts by weight: 100 parts of geopolymer precursor; 2-5 parts of sodium alginate; 13-15 parts of alkali activator; 60-62 parts of water; The alkaline activator is a water glass solution with a modulus of 1.4; The geopolymer precursor comprises the following components in percentage by weight: Red mud 45wt.%-55wt.%; Desulfurized gypsum 5wt.%-15wt.%; Fly ash 30wt.%-50wt.%.

[0006] The geopolymer material provided in this scheme for solidifying heavy metal contaminated soil, sodium alginate and Ca in desulfurized gypsum 2+ Coordination polymers are formed in the geopolymer precursor matrix and participate in the formation of NASH and CASH gels; these polymers fill the gaps left by the geopolymer hydration products, increase the cross-linking density, and enhance the compressive strength and heavy metal barrier properties; at the same time, sodium alginate can also complex or cross-link with heavy metal ions and silicate skeletons, further enhancing the solidification / stabilization effect on heavy metal contaminated soils.

[0007] Preferably, the geopolymer material for solidifying heavy metal contaminated soil comprises the following components in parts by weight: 100 parts of geopolymer precursor; 2 parts of sodium alginate; 13 parts of alkali activator; 62 parts of water.

[0008] Preferably, the geopolymer precursor comprises the following components in percentage by weight: Red mud 50wt.%; Desulfurized gypsum 10wt.%; Fly ash 40wt.%.

[0009] Preferably, the preparation method of the water glass solution with a modulus of 1.4 is: The modulus of the water glass solution with a modulus of 3.2 is reduced to 1.4 using sodium hydroxide. The Baume degree of the water glass solution with a modulus of 3.2 is 40°Bé.

[0010] In the water glass solution with a modulus of 3.2, n(SiO2) / n(Na2O)=3.2, of which the content of Na2O is 8.54%, the content of SiO2 is 27.3%, and the Baume degree is 40°Bé.

[0011] This solution also provides a method for preparing the above-mentioned geopolymer material for solidifying heavy metal contaminated soil, comprising the following steps: S1. Take sodium hydroxide solid and adjust the modulus of the water glass solution to 1.4, stir to dissolve and let stand to obtain an alkali activator; S2, mixing red mud, desulfurized gypsum and fly ash to prepare a geopolymer precursor; S3, mixing the alkali activator, sodium alginate solid and supplemented water in proportion and stirring evenly to obtain a composite alkali activator; S4, adding the composite alkali activator to the geopolymer precursor and stirring evenly to obtain the geopolymer material; Steps S2 and S3 can be switched.

[0012] Preferably, the standing time in step S1 is ≥ 24 hours.

[0013] Preferably, the stirring time in step S3 is ≥5 min.

[0014] When the geopolymer material of the present invention is used, the prepared material can be directly mixed with soil contaminated by single ions of Pb (II), Zn (II), Cu (II), and Cd (II), which is suitable for large-scale application. 2+ Coordination polymers are formed in the geopolymer matrix and participate in the formation of NASH and CASH gels. These polymers fill the gaps left by the geopolymer hydration products, increase the crosslinking density, and enhance the compressive strength and heavy metal barrier properties. At the same time, SA can also complex or crosslink with heavy metal ions and silicate skeletons, further improving the solidification / stabilization effect of heavy metal contaminated soil.

[0015] Compared with the prior art, the present invention has the following advantages: Sodium alginate reinforced composite geopolymer material SA-AGP has a significant effect in solidifying / stabilizing heavy metal contaminated soil. Compared with AGP without sodium alginate, natural material sodium alginate is introduced in the geopolymer preparation process to form an enhanced composite geopolymer material SA-AGP prepared from sodium alginate, precursors (red mud, gypsum, fly ash) and sodium silicate. The geopolymer prepared by adding sodium alginate to the alkaline activator is used to solidify / stabilize heavy metal contaminated soil, which can significantly reduce the amount of material added. In addition, due to the addition of sodium alginate, the geopolymer material SA-AGP can significantly improve the compressive strength of contaminated soil, reduce the leaching concentration of heavy metals, and convert heavy metals into a more stable form. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings: Figure 1 Schematic diagram of the preparation method of the geopolymer material of the present invention.

[0017] Figure 2 The effect of SA-AGP addition and curing time on the compressive strength of heavy metal contaminated soil; Figure 2 (a) Effect of SA-AGP on the compressive strength of zinc-contaminated soil; Figure 2 (b) Effect of SA-AGP on the compressive strength of lead-contaminated soil; Figure 2 (c) Effect of SA-AGP on the compressive strength of copper-contaminated soil; Figure 2 (d) Effect of SA-AGP on the compressive strength of cadmium contaminated soil.

[0018] Figure 3 The effect of SA-AGP addition and curing time on the toxic leaching concentration of contaminated soil; Figure 3 (a) Effect of SA-AGP on toxic leaching of zinc-contaminated soil; Figure 3 (b) Effect of SA-AGP on toxic leaching of lead contaminated soil; Figure 3 (c) Effect of SA-AGP on toxic leaching of copper contaminated soil; Figure 3 (d) Effect of SA-AGP on toxic leaching of cadmium contaminated soil.

[0019] Figure 4 is the storage form of heavy metals in soil; among them, Figure 4 (a) Effect of SA-AGP on toxic leaching of zinc-contaminated soil; Figure 4 (b) Effect of SA-AGP on toxic leaching of lead contaminated soil; Figure 4 (c) Effect of SA-AGP on toxic leaching of copper contaminated soil; Figure 4(d) Effect of SA-AGP on toxic leaching of cadmium contaminated soil. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. Example

[0021] The geopolymer precursor includes the following components in percentage by weight: Red mud 50wt.%; Desulfurized gypsum 10wt.%; Fly ash 40wt.%; The geopolymer material for solidifying heavy metal contaminated soil comprises the above geopolymer precursor and the following components in parts by weight: 100 parts of geopolymer precursor; 2 parts of sodium alginate; 13 parts of alkali activator; 62 parts of water; The preparation method of geopolymer material SA-AGP is as follows Figure 1 As shown. Take 4.8 mol of sodium hydroxide solid to adjust the modulus of 1000g of water glass solution (Baume: 40°Bé) with a modulus of 3.2 to 1.4, stir thoroughly to dissolve and let stand for at least 24 hours to obtain an alkali activator. First, red mud, desulfurized gypsum and fly ash are weighed at 50wt.%, 10wt.%, and 40wt.% respectively and mixed thoroughly to obtain a geopolymer precursor. Then, the alkali activator, sodium alginate solid and supplemented water are mixed and stirred for 5 minutes at a mass percentage of 2wt.%, 13wt.% and 62wt.% based on the total mass percentage of the geopolymer precursor solid, respectively, until completely uniform to obtain a composite alkali activator, which is then added to the geopolymer precursor and stirred evenly to obtain the geopolymer material SA-AGP. Example

[0022] The geopolymer material for solidifying heavy metal contaminated soil comprises the following components in parts by weight: 100 parts of geopolymer precursor; 5 parts of sodium alginate; 15 parts of alkali activator; 60 parts of water; The geopolymer precursor comprises the following components in percentage by weight: Red mud 45wt.%; Desulfurized gypsum 5wt.%; Fly ash 50wt.%; The preparation method of the geopolymer material is as follows: 4.8 mol of sodium hydroxide solid is used to adjust the modulus of 1000 g of water glass solution (Baume: 40°Bé) with a modulus of 3.2 to 1.4, and the solution is fully stirred and dissolved and allowed to stand for at least 24 hours to obtain an alkali activator. Red mud, desulfurized gypsum and fly ash are weighed at 45wt.%, 5wt.%, and 50wt.% respectively and thoroughly mixed to obtain a geopolymer precursor, and then the alkali activator, sodium alginate solid and supplemented water are mixed and stirred for more than 5 minutes at 5wt.%, 15wt.% and 60wt.% of the total mass percentage of the geopolymer precursor solid respectively until completely uniform to obtain a composite alkali activator, which is then added to the geopolymer precursor and stirred to obtain a geopolymer material. Example

[0023] The geopolymer material for solidifying heavy metal contaminated soil comprises the following components in parts by weight: 100 parts of geopolymer precursor; 3 parts of sodium alginate; 14 parts of alkali activator; 61 parts of water.

[0024] The geopolymer precursor comprises the following components in percentage by weight: Red mud 55wt.%; Desulfurized gypsum 15wt.%; Fly ash 30wt.%; The preparation method of the geopolymer material is as follows: 4.8 mol of sodium hydroxide solid is used to adjust the modulus of 1000 g of water glass solution (Baume: 40°Bé) with a modulus of 3.2 to 1.4, and the solution is fully stirred and dissolved and allowed to stand for at least 24 hours to obtain an alkali activator. First, red mud, desulfurized gypsum and fly ash are weighed at 55wt.%, 15wt.%, and 30wt.% respectively and thoroughly mixed to obtain a geopolymer precursor, and then the alkali activator, sodium alginate solid and supplemented water are mixed and stirred for more than 5 minutes at 3wt.%, 14wt.% and 61wt.% of the total mass percentage of the geopolymer precursor solid respectively until completely uniform to obtain a composite alkali activator, which is then added to the geopolymer precursor and stirred to obtain a geopolymer material.

[0025] The only difference between this comparative example and Example 1 is that sodium alginate is not contained; the geopolymer material comprises the following components in parts by weight: 100 parts of geopolymer precursor; 13 parts of alkali activator; 62 parts of water; The geopolymer precursor comprises the following components in percentage by weight: Red mud 50wt.%; Desulfurized gypsum 10wt.%; Fly ash 40wt.%; The preparation method of geopolymer material AGP is as follows: take 4.8 mol of sodium hydroxide solid to adjust the modulus of 1000g of water glass solution (Baume: 40°Bé) with a modulus of 3.2 to 1.4, fully stir to dissolve and stand for at least 24 hours to obtain an alkali activator. First, red mud, desulfurized gypsum and fly ash are weighed at 50wt.%, 10wt.%, and 40wt.% respectively and thoroughly mixed to obtain a geopolymer precursor, and then the alkali activator and the supplemented water are mixed and stirred for 5 minutes at 13wt.%, 62wt.% of the total mass percentage of the geopolymer precursor solids, respectively, until completely uniform to obtain a composite alkali activator, which is then added to the geopolymer precursor and stirred to obtain AGP.

[0026] According to CJJ / T 286-2018, the amount of soil solidifier added is generally 3-15% of the mass percentage of dry soil. In order to verify the influence of sodium alginate on material properties and the performance of the material, by controlling variables, the SA-AGP prepared in Example 1 and the AGP prepared in Comparative Example 1 were added to the soil contaminated by single ions of Pb (Ⅱ), Zn (Ⅱ), Cu (Ⅱ) and Cd (Ⅱ) at 3%, 6%, 12% and 15% of the mass percentage of dry soil, respectively, and the pure slurry was stirred at 80 rad / s and then loaded into a mold (diameter 50 mm, height 50 mm) to obtain a solidified sample, which was cured at room temperature (temperature 25°C, humidity 60%) (7-28 days).

[0027] Figure 2 The effects of the addition amount of SA-AGP (or AGP) (3%-15%) and curing time (7-28 days) on the compressive strength of heavy metal contaminated soil are shown. With the increase of SA-AGP addition, the unconfined compressive strength of the soil is significantly improved. Figure 2 (a) Figure 2 (b) Figure 2 (c) Figure 2 As shown in (d), when the addition amount of SA-AGP is 3wt.%, Pb 2+ 、Zn 2+ , Cu 2+ and Cd 2+ The compressive strength of the contaminated soil was 1.45, 1.60, 1.54 and 1.79 MPa, respectively, which was 103.0%, 113.9%, 50.9% and 95.83% higher than that of the 3wt.% control AGP. At the same time, the compressive strength of AGP was basically the same as that of 3wt.% SA-AGP when 6wt.% AGP was added, indicating that the introduction of SA in the preparation process of geopolymer can significantly improve the mechanical properties of the solidified soil. When the addition amount was increased to 15wt.%, SA-AGP solidified Pb after 28 days of curing. 2+ 、Zn2+ , Cu 2+ and Cd 2+ The compressive strength of the contaminated soils are 2.44, 3.62, 1.54 and 1.79 MPa respectively.

[0028] Figure 3 The effects of the addition amount of SA-AGP (or AGP) (3%-15%) and curing time (7-28 days) on the toxic leaching concentration of contaminated soil are shown. Figure 3 (a) Figure 3 (b) Figure 3 (c) Figure 3 As shown in (d), after adding 3wt.% SA-AGP and curing for 28 days, the Pb content of the solidified soil 2+ 、Zn 2+ , Cu 2+ and Cd 2+ The leaching concentrations were 1.101, 2.012, 1.569 and 1.855 mg / L, respectively, and the curing efficiencies were 83.3%, 70.7%, 74.9% and 72.7%, respectively. When 6 wt.% AGP was added, the leaching concentration was basically the same as that of 3 wt.% SA-AGP, indicating that the introduction of SA in the preparation process of geopolymer can significantly improve the blocking performance of heavy metals. After 28 days of curing with 15 wt.% SA-AGP, Pb 2+ 、Zn 2+ , Cu 2+ and Cd 2+ The leaching concentrations of the four heavy metals were 0.015, 0.712, 0.230 and 0.524 mg / L. Compared with the untreated contaminated soil, the addition of 15wt.% could reduce the leaching concentrations of the four heavy metals by more than 90%. The order of the solidification efficiency of SA-AGP for heavy metals is Pb 2+ >Cu 2+ >Cd 2+ >Zn 2+ .

[0029] Figure 4 SA-AGP can effectively convert heavy metals into a more stable residual state. Figure 4 (a) Figure 4 (b) Figure 4 (c) Figure 4 As shown in (d), Pb 2+ 、Zn 2+ , Cu 2+ and Cd 2+After 28 days of contaminated soil curing, the contents of the residual state (F4) of the solidified soil with the addition of 3wt.% SA-AGP were 46%, 17%, 30% and 35%, respectively. Compared with 3wt.% AGP, the more easily migrating acid-soluble state (F1) decreased by 30%, 8%, 10% and 11%, respectively, and the contents of the residual state (F4) increased by 38%, 20%, 14% and 9%, respectively. When the amount of SA-AGP added was increased to 15wt.%, the residual state content of heavy metals increased to 72%, 46%, 53% and 49%. After SA-AGP treatment, most of the heavy metals in the soil were converted into a stable residual state (F4), which greatly reduced the migration capacity of heavy metals. At the same time, it was once again shown that the order of SA-AGP's solidification efficiency for heavy metals was Pb, Pb-Pb, and Pb-Pb. 2+ >Cu 2+ >Cd 2+ >Zn 2+ .

[0030] In summary, the sodium alginate (SA) enhanced composite geopolymer (SA-AGP) provided in this scheme is used to solidify / stabilize heavy metal contaminated soil. Natural material sodium alginate is introduced into the preparation process of geopolymer to form an enhanced composite geopolymer (SA-AGP) prepared from sodium alginate, precursors (red mud, gypsum, fly ash) and sodium silicate. The effects of the addition amount of SA-AGP and the curing time on the unconfined compressive strength of the soil, the leaching concentration of heavy metals and the occurrence form of heavy metals are analyzed: the concentration of Pb is 500 mg / kg 2+ 、Zn 2+ , Cu 2+ and Cd 2+ After 28 days of contaminated soil curing, the compressive strength of the solidified soil with 3% SA-AGP added was 1.45, 1.60, 1.54 and 1.79 MPa, respectively, and the leaching concentration was 1.101, 2.012, 1.569 and 1.855 mg / L, respectively, which was 83.3%, 70.7%, 74.9% and 72.7% lower than that of the untreated contaminated soil, and the residual content (F4) was 46%, 17%, 30% and 35%. When the addition amount was gradually increased to 15wt.%, the residual content of heavy metals increased to 72%, 46%, 53% and 49%. The order of the efficiency of geopolymers for the solidification / stabilization of heavy metals is Pb, 2+ >Cu 2+ >Cd 2+ >Zn 2+ The geopolymer prepared by adding sodium alginate to an alkaline activator is used to solidify / stabilize heavy metal contaminated soil, which can significantly reduce the amount of material added.

[0031] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A geopolymer material for solidifying heavy metal contaminated soil, characterized in that: The composition comprises the following components in parts by weight: 100 parts of geopolymer precursor; 2-5 parts of sodium alginate; 13-15 parts of alkali activator; 60-62 parts water; The alkaline activator is a water glass solution with a modulus of 1.4; The geopolymer precursor comprises the following components in percentage by weight: Red mud 45wt.%-55wt.%; Desulfurized gypsum 5wt.%-15wt.%; Fly ash 30wt.%-50wt.%.

2. The geopolymer material for solidifying heavy metal contaminated soil according to claim 1, characterized in that: The composition comprises the following components in parts by weight: 100 parts of geopolymer precursor; 2 parts of sodium alginate; 13 parts of alkali activator; 62 parts of water.

3. The geopolymer material for solidifying heavy metal contaminated soil according to claim 2, characterized in that: The geopolymer precursor comprises the following components in percentage by weight: Red mud 50wt.%; Desulfurized gypsum 10wt.%; Fly ash 40wt.%.

4. The geopolymer material for solidifying heavy metal contaminated soil according to any one of claims 1 to 3, characterized in that: The preparation method of the water glass solution with a modulus of 1.4 is as follows: The modulus of a water glass solution having a modulus of 3.2, which has a Baume degree of 40° Bé, was reduced to 1.4 using sodium hydroxide.

5. The method for preparing a geopolymer material for solidifying heavy metal contaminated soil according to any one of claims 1 to 4, characterized in that: The steps include: S1. Take sodium hydroxide solid and adjust the modulus of the water glass solution to 1.4, stir to dissolve and let stand to obtain an alkali activator; S2, mixing red mud, desulfurized gypsum and fly ash to prepare a geopolymer precursor; S3, mixing the alkali activator, sodium alginate solid and supplemented water in proportion and stirring evenly to obtain a composite alkali activator; S4, adding the composite alkali activator to the geopolymer precursor and stirring evenly to obtain the geopolymer material; Steps S2 and S3 can be switched.

6. The method for preparing a geopolymer material for solidifying heavy metal contaminated soil according to claim 5, characterized in that: The standing time in step S1 is ≥ 24 hours.

7. The method for preparing a geopolymer material for solidifying heavy metal contaminated soil according to claim 5, characterized in that: The stirring time in step S3 is ≥5 min.

Citation Information

Patent Citations

  • Red mud geology polymeric material recipe and preparation method thereof

    CN106477985A

  • PROCESS FOR OBTAINING SYNTHETIC GEOPOLYMERS AND SYNTHETIC GEOPOLYMERS

    BR102021018318A2

  • Method for stabilizing and solidifying heavy metal ions in incineration flying ash

    CN107596613A

  • Preparation method of silica gel-based adsorbent for heavy metals

    CN109550486A

  • Method for immobilizing and neutralizing arsenic in slag by using fly ash-red mud based geopolymer

    CN114988728A